(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
Uzbekistan dated March 19, 2021 " On measures to increase the quality of education in the field of physics and develop scientific research". In order to ensure the implementation of the decision , a number of works are being carried out to improve the quality of physics teaching in educational institutions, to introduce modern teaching methods to the educational process , to select talented students , and to prepare competitive specialists for the labor market . In particular, the involvement of students in the process of active learning , the main goal of which is the use of interactive methods in education . This requires cooperation between the student and the teacher. The teacher should attract students to the problems related to the subject of the lesson , activate their movement and , as a result , ensure their guaranteed mastery .